Confined growth of thin mordenite films into microreactor channels - Zamaro, Juan Manuel (2009)
This communication presents the production of a mordenite film growth totally confined into 350 μm wide microchannels on copper alloy plates for microreactor preparation. The growth is obtained in open channel configuration by secondary synthesis after 12 h of treatment over this highly thermal conductivity support. The confined growth presents a high overall quality. It is crystalline, uniform, and adherent; it totally covers the microchannels surface and has 5 μm. These properties are confirmed by XRD, SEM and EPMA characterizations.